Handheld Digital TV Performance Evaluation Method - Gunnar Bedicks; Fujio Yamada; Francisco Sukys; Cristiano Akamine; Luis Tadeu Raunheitte; Edson L. Horta (International Journal of Digital Multimedia Broadcasting)
This paper presents a simplified method for signal level clearance evaluation in each place of signal reception up to threshold for a given portable TV receiver device. It describes briefly the structure of transmission system considering the “1Seg” structure of ISDB-T. The preliminary laboratory test was made before the field tests to verify the main features of handheld receiver.